PERTANGGUNGJAWABAN HUKUM OLEH RUMAH SAKIT ATAS PENOLAKAN MEDIS PASIEN TIDAK MAMPU BERDASARKAN UNDANG-UNDANG NOMOR 44 TAHUN 2009 - Saraswati, Yuliana Putri; Hufron, Hufron (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to analyze legal liability by hospitals for medical refusal by underprivileged patients, researchers use a type of normative legal research aimed at examining the rules surrounding hospital refusal responsibility for vulnerable patients. Covers the study of legal principles, legal rules and legal systematics. The main legal basis comes from statutory regulations, and the secondary legal basis is in the form of literature, documents, opinions of legal experts. This is also related to legal protection for underprivileged patients. If doctors and other medical personnel only act as employees, the hospital must take full responsibility for the patient. The legal status of medical care for the most vulnerable patients is found in Article 190 Paragraph (1) of Health Law No. 36 of 2009. A patient who feels aggrieved by the hospital's refusal to provide medical treatment can sue the hospital administration in a civil court and has the right to get a replacement in accordance with Article 58 Paragraph (1) Health Law No. 36 of 2009 and Article 32 letter q Hospital Law No. 44 of 2009. Refusal of medical services to patients who need urgent care, including actions that are detrimental to patients, are regulated in Articles 1365, 1366 and 1367 of the Civil Code